Kenya : First Review Under the Twelve-Month Stand-By Arrangement and the Arrangement Under the Stand-By Credit Facility, Request for Waivers for Non-Observance of Performance Criterion, and Request for Modification of Performance Criteria-Press Release; Staff Report; and Statement by the Executive Director for Kenya. - International Monetary Fund. African Dept. (Washington, D.C. : International Monetary Fund, 2015)
This paper discusses Kenya's First Review Under the Twelve-Month Stand-by Arrangement and the Arrangement Under the Standby Credit Facility, Request for Waivers for Nonobservance of Performance Criterion (PC), and Request for Modification of PC. All quantitative PCs for end-March 2015 were met, but the continuous performance criterion on external arrears was not observed owing to the emergence of temporary technical arrears on external debt. The IMF staff recommends completion of the first review and supports the authorities' request for a modification of PCs for end-September 2015, and for waivers for nonobservance of the PCs on external arrears.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet